2017
DOI: 10.1055/s-0037-1604325
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors of Toxocara canis Infection in Children (2–15 Years Old) Referred to Health Centers of Lorestan Province, Iran

Abstract: This study aims to evaluate the seroprevalence and risk factors for Toxocara canis infection in children (2–15 years old) referred to health centers of Lorestan province, Iran. This cross-sectional study was performed from August 2016 to March 2017 on 316 children. All serum samples were tested using the commercially available anti IgG-Toxocara kit (IBL, Germany) according to manufacturer's instructions. Of the 316 children, 14 (4.4%) tested seropositive for anti-T.canis IgG antibody. The variables used to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
1
3
1
Order By: Relevance
“…Also, Nourian et al [29] agreed with our study determined 4.4% cases in rural areas and 1.6% cases in urban areas. Similar results also reported in another study [42] which reported 11.9% cases in rural areas and 2.1% cases in urban areas.…”
Section: Discussionsupporting
confidence: 91%
“…Also, Nourian et al [29] agreed with our study determined 4.4% cases in rural areas and 1.6% cases in urban areas. Similar results also reported in another study [42] which reported 11.9% cases in rural areas and 2.1% cases in urban areas.…”
Section: Discussionsupporting
confidence: 91%
“…20 Our finding showed similar prevalence which reported in Shiraz (18.26%) 21 , while lower prevalence was reported in Lorestan (4.4%). 22 Other studies in Tehran and Mazandaran reported higher prevalence than our study, but lower than the national seroprevalence. 23,24 The Seroprevalence rate of Toxoplasma gondii infection was showed a wide range from 4 to 84% depending on the environmental and socio-economic conditions from different parts of the world.…”
Section: Discussioncontrasting
confidence: 69%
“…In the current study, no statistically significant differences were seen between seropositivity to Toxocara infection and eating un-cooked/raw vegetable. There was no significant difference between consumption of raw/unwashed vegetables and T. canis seropositivity in children (2–15 yr old) referred to Health Centers of Lorestan Province, Iran ( 32 ). Children having history of eating raw vegetable are more infected with Toxocara (36.84%) compare with children have not history of eating raw vegetable (25.84%) ( 19 ).…”
Section: Discussionmentioning
confidence: 93%